Investigation of Carbapenem resistance mechanisms in Klebsiella pneumoniae by using phenotypic tests and a molecular assay - Esra Ciftci; Emel Sesli Cetin; Ebru Us; Hüseyin Haydar Kutlu; Buket Cicioglu Arıdogan (Journal of Infection in Developing Countries)
Introduction: The aim of this study was to investigate the presence of carbapenemase production and carbapenem resistance mechanisms in 47 carbapenem resistant Klebsiella pneumoniae isolates by phenotypic confirmatory tests and molecular assay.